Numerical Optimization of Metamaterial-Enhanced Infrared Emitters for Ultra-Low Power Consumption - Bui Xuan Khuyen; Pham Duy Tan; Bui Son Tung; Nguyen Phon Hai; Pham Dinh Tuan; Do Xuan Phong; Do Khanh Tung; Nguyen Hai Anh; Ho Truong Giang; Nguyen Phuc Vinh; Nguyen Thanh Tung; Vu Dinh Lam; et al. (Photonics, 2025)
This study addresses the challenges of high-power consumption and complexity in conventional infrared (IR) gas sensors by integrating metamaterials and gold coatings into IR radiation sources to reduce radiation loss. In addition, emitter design optimization and material selection were employed to minimize conduction loss. Our metasurface exhibited superior performance, achieving a narrower full width at half maximum at 4197 and 3950 nm, resulting in more confined emission spectral ranges. This focused emission reduced energy waste at unnecessary wavelengths, improving efficiency compared to traditional blackbody emitters. At 300 °C, the device consumed only 6.8 mW, while maintaining temperature uniformity and a fast response time. This enhancement is promising for the operation of such sensors in IoT networks with ultra-low power consumption and at suitably low costs for widespread demands in high-technology farming.